Monday

April 27, 2015

April 27, 2015

Posted by **Terri** on Tuesday, February 24, 2009 at 8:52pm.

2x-y+z=3

x+3y-2x=11

3x-2y+4z=1

- algebra -
**Reiny**, Tuesday, February 24, 2009 at 9:51pmdouble the first equation, then add that to the second to get

5x+y = 17

double the second, then add that to the third to get

5x + 4y = 23

now subtract those last two equations to get

3y = 6

y = 2

put that into 5x + y = 17 for

5x = 15

x = 3

now in the first

6 - 2 + z = 3

z = -1

I assumed your second equation had -2z at the end. typo ??

- algebra -
**Terri**, Tuesday, February 24, 2009 at 10:22pmThanks, yes, typo

I just finished solving it a long way, I solved the first two, then the second two,,etc etc. Your way seems much easier, I did get the same answers, yeah!!!! But, will your way always work?